Risk factors for major amputation after arterial vascular trauma of the lower extremity. (February 2022) - Kluckner, Michaela; Gratl, Alexandra; Gruber, Leonhard; Frech, Andreas; Gummerer, Maria; Wipper, Sabine; Enzmann, Florian K.; Klocker, Josef
Background & objective: Arterial vascular trauma bears a great risk of poor functional outcome or limb loss. The aim of this study was to analyze amputation rates of patients after vascular trauma and to perform a predictor analysis for the risk of major amputation. Methods: In a single-center retrospective analysis of 119 extremities treated for arterial vascular injury between 1990 and 2018 amputation rates and factors associated with limb loss were assessed. All patients were treated for traumatic vascular injuries; iatrogenic injuries were not included in the study. Results: During the study period, a total of 119 legs in 118 patients were treated after arterial vascular trauma. The in-hospital major amputation rate was 16.8% and the mortality rate was 2.5%. In the predictors analysis, vascular re-operation (amputation rate 53.8% vs 12%, odds ratio = 8.56), a Rutherford category ⩾IIb (25.4% vs 4.2%, odds ratio = 6.43), work-related or traffic accidents (28.2% vs 0%, odds ratio = 4.86), concomitant soft tissue or bone injuries (26.7% vs 7.3%, odds ratio = 4.64), polytrauma (33.3% vs 12%, odds ratio = 3.68), and blunt trauma (18.9% vs 0% for penetrating trauma, odds ratio = 1.64) were found to be associated with amputation. Conclusions: Lower extremity arterial vascular trauma was associated with a significant major amputation rate. Several predictors for limb loss were identified, which could aid in identifying patients at risk and adapting their treatment.